Reflections on community-based participation to reduce violent crimes in South Africa. Issue 4 (1st October 2020) - Govender, Doraval
ABSTRACT: This article reflects on community-based participation to reduce violent crimes in South Africa. Despite many policing strategies being developed and implemented over the years to reduce violent crimes in South Africa, these crimes are still on the increase. Against this background, the researcher reflects on some of the perceptions of violent crimes and policing that erode public confidence daily. The study is essentially qualitative in its approach. The researcher used the snowball sampling technique to identify community members from the Tshwane metropolitan area in Gauteng for in-depth interviews. The findings revealed that community members were unhappy with the level of community participation in the day-to-day policing of violent crimes in communities. This alienated them from the police and had an adverse effect on the ability of the police to enforce safety and security in communities. In view of these findings, there is a need for the police to enhance community participation so that the needs and expectations of communities are given priority.